relationship be1ween erosion and accumulation of sediments in coastal zone of binh thuan province· south central of vietnam - Nghi, Tran; Tien, Dao Manh; Thanh, Dinh Xuan; Lan, Nguyen Thanh (VNU Journal of Science: Natural Sciences and Technology, 2005)
Abstract